Ionically Modified Cellulose Nanocrystal Self-Assembled Films with a Mesoporous Twisted Superstructure: Polarizability and Application in Ion-Gated Transistors - Grey, Paul (2020)
FCT – Portuguese Foundation for Science and Technology through the Ph.D. scholarship SFRH/BD/125191/2016. project PapEl, reference PTDC/CTM-NAN/5172/2014. project CHIHC, reference PTDC/NAN-MAT/32558/2017. project PTDC/CTM-BIO/6178/2014, M-ERA-NET2/0007/2016 (CellColor). POR Lisboa2020 through project PTDC/CTM-REF/30529/2017. D.G. acknowledges the support from FCT – Portuguese Foundation for Science and Technology through the AdvaMTech PhD program scholarship PD/BD/52627/2014.